The effect of high intensity interval and continues training on cardiac stem cells function and myocardial regeneration capacity in male rats - AREZOO ESKANDARI SHAHRABI; rahman sori; siroos chobineh; zohre mazaheri tirani (Shahid Beheshti University, 2019)
Purpose: Adult cardiac stem cells have ability to regenerate and repair cardiac cells through proper stimulation. Cardiac regeneration capacity decreases with ageing, while physical activities play a positive role in this case. The aim of this study was the effect of high intensity interval and continues training on cardiac stem cells function and myocardial regeneration capacity in male rats.Methods: Twenty-four Vistar male rats (365.6±13.3 g, 6-8 month) were divided into three groups HIIT (high intensity) continuous and control. The training protocol was performed 5 sessions per week for 6 weeks. The heart rats were extracted and c-Kit and Ki67 values were analyzed by Immunohistochemistry and Nkx2.5 gene expression for cardiac stem cells was measured by Real Time-PCR. The data were analyzed by one-way ANOVA (P≤0.05).Results: According to the results of this study, there was a significant increase in c-Kit cells in the HIIT (P=0.001) and in the continuous group (P=0.018) and Significant increase in positive Ki67 cells in the HIIT group (P=0.001) and continuous group (P=0.05). This increase was greater in the HIIT group. As well as a significant increase was observed in the Nkx2.5 gene expression in the HIIT training group (P=0.015) and in the continuous group (P=0.03) which increased in the continuous group was grater.Conclusion: The results showed that the intensity of training is more effective for cardiac regeneration adaptation and HIIT have more positive effects on differentiation of cardiac stem cells.